Defending human dignity : the role of the human rights activist and the scholar / Fons Coomans (editor). - Coomans, Fons (Theo van Boven lecture series, 2017)
This booklet contains the texts of the Theo van Boven Lectures held in 2014 and 2015. They deal with the subject of defending human dignity by looking at the different roles the human rights defender, the scholar and the human rights NGO can play in achieving this goal. Hina Jilani looks at the opportunities and limitations of human rights defenders in their fight to stand up for the protection of human dignity. Jean Allain discusses the role of the legal scholar in studying contemporary forms of slavery. Finally Aidan McQuade denounces practices of slavery from the perspective of a human rights NGO. The Theo van Boven Lecture Series are organised annually by the Maastricht Centre for Human Rights as a tribute to Theo van Boven, emeritus Professor of International Law at Maastricht University, and formerly Director of the UN Division of Human Rights, member of the Committee on the Elimination of Racial Discrimination and UN Special Rapporteur on Torture. The themes covered by the lectures reflect the wide range of interests of Theo van Boven. This publication is interesting for human rights practitioners, scholars and students.